Diferentes densidades de estocagem na larvicultura do trairão Hoplias lacerdae - Luz, Ronald Kennedy [UNESP]; Portella, Maria Célia [UNESP] (Universidade Estadual de Maringa, 2005)
This experiment was carried out to evaluate the effects of the stocking density on trairao larvae rearing. Seven days old larvae were submitted to four different stocking densities: 10, 30, 60 and 90 larvae/L. Sixteen vessels with 5 L each supplied with constant aeration were kept in a thermostatic bath. Each treatment had four replications. In order to keep the internal environment dark, all the experimental units were covered with a black plastic and it was uncovered only during the daily management. At the end of the experiment, after 15 days of feeding with Artemia nauplii, no significant differences were found (P>0.05) on growth among the evaluated densities. The same results were also registered for the survival, mortality and cannibalism rates. Higher stocking density resulted in higher production of trairao larvae rearing, allowing intensive rearing of this species in this phase.
Different stocking densities in trairão (Hoplias lacerdae) larvae rearing
Keywords: Hoplias lacerdae; Intensive fish larva rearing; Stocking density; Trairão; aeration; Artemia; cannibalism; feeding; larva; mortality; nonhuman; rearing; stocking density; survival; vessel; Hoplias